APLIKASI FILTER KERAMIK BERBASIS TANAH LIAT ALAM DAN ZEOLIT PADA PENGOLAHAN AIR LIMBAH HASIL PROSES LAUNDRY - Nasir, Subriyer (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstract Ceramic filters made of natural clay and zeolite were used to treat the efluent from laundry industry in Palembang. The pretreatment process using silica and active carbon was applied to the samples prior feed to the ceramic filter. Process variables studied were operating time and the filters composition. Parameters analyzed were TDS (Total Dissolved Solid), pH, EC (Electrical Conductivity), COD (Chemical Oxygen Demand), BOD (Biological Oxygen Demand) and the concentration of LAS (Linear Alkylbenzene Sulphonate). The results showed that ceramic filters combined with silica and activated carbon can reduce the LAS concentration in detergent wastewater up-to 97%. Scanning Electron Microscope (SEM) images shows that filter could be categorized as microfiltration filter with random porous structures.
Keywords: Keywords: ceramic filter, microfiltration, laundry, wastewater, natural clay, zeolite